2016
DOI: 10.1007/s00005-016-0408-8
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Side of Disodium Cromolyn: from Mast Cell Stabilizer to an Angiogenic Factor and Antitumor Agent

Abstract: Scattered data suggested that disodium cromolyn, well known as a mast cell stabilizer shows some effects on tumor cells and tumor-associated newly formed vascular networks. Most of these studies used tumor cell lines assessed by in vitro studies. Nor disodium cromolyn effects on melanoma cell lines were studied yet, neither its influence on recruited tumor blood vessels or angiogenic growth factors expression. We designed here a study regarding disodium cromolyn effects on A375 melanoma tumor cells implanted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our results confirmed the importance of the vascular network in the dynamic behavior of the Bio-Gen implant, but at the same time, it was pointed out that the development of the vascular network is dependent on the resuspension media. Based on the results previously described in this paper, the resuspension of bone granules in hyaluronic acid represents the optimal technique for the success of the implant, due to both anti-inflammatory and angiogenic effects that are well-known and cited in the literature [20]. A distinct aspect of the present experimental research is represented by the observation of the osteoinduction on CAM mesenchymal cells with a particular stratified distribution, as described in the results section.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results confirmed the importance of the vascular network in the dynamic behavior of the Bio-Gen implant, but at the same time, it was pointed out that the development of the vascular network is dependent on the resuspension media. Based on the results previously described in this paper, the resuspension of bone granules in hyaluronic acid represents the optimal technique for the success of the implant, due to both anti-inflammatory and angiogenic effects that are well-known and cited in the literature [20]. A distinct aspect of the present experimental research is represented by the observation of the osteoinduction on CAM mesenchymal cells with a particular stratified distribution, as described in the results section.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, CAM is an embryonic tissue lacking an immune system and having mesenchymal cells with stem like potential able to differentiate depending on a specific microenvironment [15,16]. Based on the previously described features, CAM is a reliable in vivo model for testing the behavior of normal and pathologic tissues (as cultured cells or malignant tumors) [17,18], of different drugs and antibodies [19,20], or of a variety of biomaterials implanted on its surface [21,22]. There is minimal data available regarding bone implants on CAM [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between MC density of tumors, the progression of angiogenesis, and tumor development may highlight the possible role of MCs in tumor biology. Therefore, the possibility of targeting MC activation [67,68], inhibiting the release of mediators using c-Kit receptor tyrosine kinase inhibitors (TKI) (including imatinib, masitinib [69]), or using tryptase inhibitors (mainly gabexate mesylate and nafamostat mesylate, both inhibitors of trypsin-like serine proteases [69,70]) may be valuable therapeutic approaches to control the tumor development [71]. Masitinib, a TKI that targets c-kit receptors (CD117), has been used in veterinary medicine for years, and lately, human clinical trials were initiated to test its clinical efficacy as single or add-on treatment human cancers such as mastocytosis, gastrointestinal stromal tumors (NCT00998751), colon cancer (NCT03556956), prostate cancer (NCT03761225), and pancreatic cancer (NCT03766295) [72].…”
Section: Mcs As Therapeutic Targetsmentioning
confidence: 99%
“…Cromolyn sodium can inhibit the function of mast cells and increase the efficacy of immunotherapy. Cromolyn sodium, a classic stabilizer of the mast cell membrane, can inhibit degranulation [ 33 ]. We confirmed that the enhancement effect of PD-1 antibody on mast cells could be partially weakened by pretreatment with 10 μg/ml cromolyn sodium for 1 h before treatment with PD-1 antibody.…”
Section: Discussionmentioning
confidence: 99%